Late Jurassic Nb‐enriched basalts from the Bilong Co area in the southern Qiangtang Terrane, central Tibet, and their implications. Issue 1 (19th November 2021) - Cheng, Jianbo; Li, Yalin; He, Haiyang; Xiao, Siqi; Bi, Wenjun; Zou, Yu
Abstract : Arc‐related magmatic records in the southern Qiangtang Terrane play a key role in the complete understanding of the tectonic evolution of the Bangong–Nujiang Ocean during the late Mesozoic. In this study, we present new zircon U–Pb ages, whole‐rock geochemical, and Sr–Nd isotopic data for the Bilong Co basalts in the central segment of the southern Qiangtang Terrane. The results show that the studied basalts were most likely emplaced during the Kimmeridgian (Late Jurassic). They are characterized by low SiO2 (49.48–52.55 wt%), and high Al2 O3 (14.75–15.89 wt%) and MgO (7.44–9.16 wt%), and belong to the high‐K calc‐alkaline to shoshonite series. All samples show significant enrichment in light rare earth elements (LaN /YbN  = 14.99–17.47) and large‐ion lithophile elements, but depletion in high‐field‐strength elements with pronounced negative Nb‐Ta‐Ti anomalies. Six samples exhibit constant and depleted whole‐rock εNd (t) values ranging from 5.78 to 6.03. The Bilong Co basalts have high Nb (6.47–9.52 ppm) contents and Nb/Yb (3.49–4.30) ratios, which resemble those of the arc‐related Nb‐enriched basaltic rocks in the southern Qiangtang Terrane. These geochemical signatures reveal that the Bilong Co basalts were most likely derived from a mantle wedge metasomatized by slab‐derived melts and sediments in a continental arc setting, indicating the northward subduction of the Bangong–Nujiang oceanic lithosphere beneath the southern Qiangtang Terrane during the Late Jurassic. Our results, together with the previously published data, suggest that the Late Jurassic arc‐related magmatism is rather extensive in the southern Qiangtang Terrane, further supporting a Cretaceous closure of the Bangong–Nujiang Ocean. Abstract : The Nb‐enriched Bilong Co basalts in the central segment of the southern Qiangtang Terrane were emplaced during the Kimmeridgian (Late Jurassic). Their geochemical signatures reveal that they were most likely derived from a mantle wedge metasomatized by slab‐derived melts and sediments in a continental arc setting, indicating the northward subduction of the Bangong–Nujiang oceanic lithosphere beneath the southern Qiangtang Terrane during the Late Jurassic, further supporting a Cretaceous closure of the Bangong–Nujiang Ocean.